A comprehensive review of Nε-carboxymethyllysine and Nε-carboxyethyllysine in thermal processed meat products. (April 2020) - Zhu, Zongshuai; Huang, Ming; Cheng, Yiqun; Khan, Iftikhar Ali; Huang, Jichao
Abstract: Background: N ε -carboxymethyllysine (CML) and N ε -carboxyethyllysine (CEL) are two typical advanced glycation end products (AGEs) formed at the advanced stage of Maillard reaction. CML and CEL are easily formed in thermal processed meat products for the high levels of protein and fat, causing sorts of chronic diseases. However, there is lack of comprehensive review on the CML and CEL formation mechanism, determination and inhibition methods in processed meat. Scope and approach: In order to better monitor and control the levels of AGEs in processed meat products. The present review summarized the CML and CEL formation mechanism based on the oxidation and Maillard reaction, the mass spectrometry and kit measurement methods, as well as the inhibition strategies in processed meat. Key findings and conclusions: Firstly, different levels of oxidation play an important role on CML and CEL formation in thermal processed meat. Secondly, mass spectrometry identification and analysis is the main method for measuring the levels of free and protein-bound CML and CEL. Finally, ameliorating the thermal processing and adding polyphenol in meat products are two best ways for CML and CEL inhibition. Some useful suggestions are concluded for the CML and CEL reduction in home cooking and industrial production. Highlights: CML and CEL formation based on the oxidation and Maillard reaction. Mass spectrometry and kit measurement applied to CML and CEL. Ameliorating processing and adding polyphenol for AGEs inhibition. Suggestions for the CML and CEL reduction in processed meat.